1983
DOI: 10.1073/pnas.80.21.6662
|View full text |Cite
|
Sign up to set email alerts
|

Composition and distribution of low density lipoprotein fractions in hyperapobetalipoproteinemia, normolipidemia, and familial hypercholesterolemia.

Abstract: Hyperapobetalipoproteinemia is defined as the combination of a normal low density lipoprotein (LDL) cholesterol in the face of an increased LDL apolipoprotein B (apoB) protein.To examine the physical basis for the apparent disproportion between LDL cholesterol and apoB characteristic of this syndrome, we used density gradient ultracentrifugation to isolate LDL fractions from 10 normal subjects, from 20 patients with hyperapobetalipoproteinemia (10 normotriglyceridemic and 10 hypertriglyceridemic), and from 7 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(68 citation statements)
references
References 36 publications
4
64
0
Order By: Relevance
“…The percent content of cholesterol was significantly lower in survivors than in controls, whereas the percent content of apolipoprotein was rather higher in survivors, resulting in a lower cholesterol to apolipoprotein ratio of LDL in survivors (1.08±0.17) than that in controls (1.20±0.13) (Teng et al 1983), although not statistically significant. The percent content of either phospholipid or triglyceride did not differ between survivors and controls (Table 4).…”
Section: Low Density Lipoprotein (Ldl)mentioning
confidence: 77%
See 1 more Smart Citation
“…The percent content of cholesterol was significantly lower in survivors than in controls, whereas the percent content of apolipoprotein was rather higher in survivors, resulting in a lower cholesterol to apolipoprotein ratio of LDL in survivors (1.08±0.17) than that in controls (1.20±0.13) (Teng et al 1983), although not statistically significant. The percent content of either phospholipid or triglyceride did not differ between survivors and controls (Table 4).…”
Section: Low Density Lipoprotein (Ldl)mentioning
confidence: 77%
“…On the other hand, LDL, a major cholesterol transporting lipoprotein, is considered not to be homogeneous. Sniderman et al (1980) claimed that the plasma concentration of LDL apolipoprotein (apo B) may frequently be increased in patients with coronary heart disease despite their having an LDL cholesterol within the normal range and this abnormality is pronounced in not heavy but light LDL particles (Sniderman et al 1980;Teng et al 1983). It was shown by these investigators that cholesterol to apolipoprotein B ratio in coronary heart disease is significantly lower than that in control when light subfraction of LDL was examined (Teng et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The first feature of hyperapoB to be recognized was the elevated LDL particle number, many of which are smaller and denser than normal [4]. In reality, though, the metabolism of all the lipoprotein classes is demonstrably abnormal.…”
mentioning
confidence: 99%
“…The less dense subtraction was enriched in triglycerides, and the more dense subtraction was poor in lipids and had an unusually high ratio of apo B to cholesterol. Previously, Teng et al 11 had reported that denser LDL in patients with hyperapobetalipoproteinemia has a high content of apo B. Many patients with hyperapobetalipoproteinemia probably have familial combined hyperiipidemia -a condition in which very dense LDL have also been reported.…”
Section: Metabolism Of Polydlsperse Ldlmentioning
confidence: 99%